Patients' attitude toward diabetes mellitus screening in Thai dental clinics - Chanita Tantipoj; Narin Hiransuthikul; Sirirak Supa-amornkul; Vitool Lohsoonthorn; Siribang-on Piboonniyom Khovidhunkit (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - Diabetes mellitus (DM) is an important health problem throughout the world. Association between DM and oral diseases has been reported and dental clinic is indicated to be one of the suitable venues for the screening of DM. The purpose of this paper is to determine patients' attitude toward DM screening in dental clinics. Design/methodology/approach - The anonymous, self-administered questionnaires of five-point response scale questions were distributed to convenience samples of adult patients (⩾25 years) attending one of the dental settings. These dental settings were divided into the university/hospital-based dental clinics (encompassing two university-based and five hospital-based dental clinics) or the private dental clinics (encompassing two private, and one special (after office hour) clinic of a faculty of dentistry). The questions could be categorized into three groups regarding importance, willingness, and agreement of DM screening in dental settings. Results are presented as percentage by respondents based upon the number of responses for each question. The favorable outcomes which were defined as responses of either scale of 4 or 5 were also summarized according to dental settings. The χ2 test for comparison was used to compare the favorable outcomes between the two settings. Findings - A total of 601 completed questionnaires were collected; 394 from university/hospital-based dental clinics and 207 from two private clinics and a special (after office hour) clinic of a faculty of dentistry. Overall, the majority of respondents in both university/hospital-based and private practice settings felt that it is important to have a dentist conduct a screening (84.8 vs 79.5 percent). The majority of patients in both groups were willing to receive blood pressure examination (95.0 vs 92.0 percent), weight and height measurements (94.7 vs 94.0 percent), saliva/oral fluid investigation (86.4 and 86.9 percent) and finger-stick blood test (83.8 vs 83.9 percent). More than 75 percent of all respondents agreed with diabetes screening in dental clinics. Originality/value - The majority of respondents supported the screening of DM in dental settings and they were willing to have a screening test by the dentist. Patient acceptance is an important key to be successful in the screening of DM in dental settings.